Soil microbial interconnections along ecological restoration gradients of lowland forests after slash-and-burn agriculture. Issue 5 (26th April 2021) - Lin, Qiang; Dini-Andreote, Francisco; Li, Lingjuan; Umari, Ruma; Novotny, Vojtech; Kukla, Jaroslav; Heděnec, Petr; Frouz, Jan
ABSTRACT: Microbial interconnections in soil are pivotal to ecosystem services and restoration. However, little is known about how soil microbial interconnections respond to slash-and-burn agriculture and to the subsequent ecosystem restoration after the practice. Here, we used amplicon sequencing and co-occurrence network analyses to explore the interconnections within soil bacterial and fungal communities in response to slash-and-burn practice and a spontaneous restoration (spanning ca. 60 years) of tropical forests after the practice, in Papua New Guinea. We found significantly higher complexity and greater variations in fungal networks than in those of bacteria, despite no significant changes observed in bacterial or fungal networks across successional stages. Within most successional stages, bacterial core co-occurrences (co-occurrences consistently present across all sub-networks in a stage) were more frequent than those of fungi, indicating higher stability of interconnections between bacteria along succession. The stable interconnections occurred frequently between bacterial taxa (i.e. Sporosarcina, Acidimicrobiale and Bacillaceae ) and between ectomycorrhizal fungi ( Boletaceae and Russula ochroleuca ), implying important ecological roles of these taxa in the ecosystem restoration. Collectively, our results provide new insight into microbial interconnections in response to slash-and-burn agriculture and the subsequent ecosystem restoration, thus promoting a better understanding of microbial roles in ecosystem services and restoration. Abstract : Interconnections between bacteria were more stable but less complex than interconnections between fungi along restoration of lowland forests.